The Effect of Think Pair and Share Learning Model Assisted by Pop Up Book Media on Fifth Grade Students' Mathematics Learning Outcomes - Vira Nur Hasanah; Hema Widiawati; Dianasari Dianasari (Journal of Educational Sciences, 2026)
This study was motivated by the low mathematics learning outcomes in fractions among fifth-grade students at SDN 1 Dawuan due to conventional teaching methods and limited learning media. The study aimed to examine the effect of the Think Pair and Share (TPS) learning model assisted by Pop Up Book media on students’ cognitive learning outcomes. This study differs from previous research by integrating TPS and Pop Up Book media in fraction learning. A quantitative quasi-experimental design with a Two-Group Pretest Posttest Non-Equivalent Control Group was employed. The sample consisted of 42 students, including 21 students in the experimental group and 21 students in the control group. Data were collected using a validated multiple-choice test. The results showed that the experimental group’s mean score increased from 31.11% to 58.41%, while the control group’s score increased from 32.38% to 38.41%. The N-Gain score of 0.3315 indicated moderate effectiveness, and the Independent Samples T-Test yielded a significance value of 0.000 (< 0.05). The findings indicate that TPS assisted by Pop Up Book media effectively improves students’ mathematics learning outcomes on fraction material through collaborative and visual learning experiences.